If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x+9)=-44+32
We move all terms to the left:
4(2x+9)-(-44+32)=0
We add all the numbers together, and all the variables
4(2x+9)-(-12)=0
We add all the numbers together, and all the variables
4(2x+9)+12=0
We multiply parentheses
8x+36+12=0
We add all the numbers together, and all the variables
8x+48=0
We move all terms containing x to the left, all other terms to the right
8x=-48
x=-48/8
x=-6
| 2(6x-1)+2(2x+5=120 | | j+13=28 | | -5p-5=95 | | -5+n/25=1 | | 5(3x+7)=-42+47 | | -0.41+0.98x=1.341 | | 9=f+3 | | 5−(-2z)=7 | | 7/5x+3x=15 | | 20(-12+v)=420 | | 4/x=28/63 | | 6(3-7b)-4b=110 | | 3/8(-7y+8)+1/3y=17/24 | | 22=5x=6-3x | | 4(5x-3+5x+5=118 | | x/8=1/2=6 | | -14-14x=462 | | X+2x+17=180 | | 12+8n=-n-6 | | -13+r/8=-14 | | g−52=-12 | | 5a-10=3a-10 | | 216=8(6p+3) | | 7=h+1 | | 14+p/4=8 | | 7(y-2)/2=-3y | | 9x+14=7x+22 | | j−3=36 | | j−1=7.4 | | 2(7z-7=14 | | 9+v/10=3 | | 3=-5+x+6 |